2016
DOI: 10.17061/phrp2631631
|View full text |Cite
|
Sign up to set email alerts
|

Generating qualitative data by design: the Australian Longitudinal Study on Women’s Health qualitative data collection

Abstract: Objectives and importance of study: The purpose of this study was to illustrate how qualitative free-text comments, collected within the context of a health survey, represent a rich data source for understanding specific phenomena. Study type:Work conducted with data from the Australian Longitudinal Study on Women's Health (ALSWH) was used to demonstrate the breadth and depth of qualitative information that can be collected. The ALSWH has been collecting data on women's health since 1996, and represents a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…; Tavener et al. ; Terry & Braun ). These comments have successfully been utilised to explore multifaceted and complex health experiences of women, ranging from contraceptive use to widowhood (see e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Tavener et al. ; Terry & Braun ). These comments have successfully been utilised to explore multifaceted and complex health experiences of women, ranging from contraceptive use to widowhood (see e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We selected comments based on participant's quantitative responses, a process akin to identifying a sampling frame from which the data for analysis are drawn (Tavener et al. ). Our sampling frame therefore included women who reported that they provide care for their or their partners’ children at Survey 7 (regardless of the age of their child/children), and regardless of whether women were engaged in paid employment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women's experiences of childbirth and maternity care were measured using 7-point scales; the results of the quantitative analysis will be published separately. In this paper, we report on the analysis of participants' free text comments which provided rich and valuable information and are considered a data source in their own right (Tavener et al, 2016). While the survey included eight statements that allowed free text responses, this paper focussed only on the following statements: 1) Please describe any things about your pregnancy that you were particularly happy with;…”
Section: Data Collectionmentioning
confidence: 99%